The effect of clonazepam on myoclonic seizures in infancy and childhood - Aysun, Sabiha; Renda, Yavuz (The Turkish Journal of Pediatrics, 1978)
This study was undertaken to investigate the effect of clonazepam on myoclonic seizures. The drug was administered to two groups of patients: first group consisted of patients who had never taken any anticonvulsants, second group consisted of patients who had been treated with one or more anticonvulsant with no success. The effect of clonazepam was investigated in relation with the onset of the disease, the duration, and the frequency of the seizures, the effect of clonazepam was found to be more pronounced with patients whose seizures started after the age of six months and in the patients whose disease started more than one year prior to the study and in those with fewer attacks.